2005
DOI: 10.1186/ar1730
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hyaluronan (HA), an important component of connective tissues, is highly metabolically active, but the mechanisms involved in its catabolism are still largely unknown. We hypothesized that a protein similar to sperm PH-20, the only mammalian hyaluronidase known to be active at neutral pH, could be expressed in connective tissue cells. An mRNA transcript similar to that of PH-20 was found in chondrocytes, synoviocytes, and dermal fibroblasts, and its levels were enhanced upon stimulation with IL-1. In cell laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 52 publications
(72 reference statements)
0
6
0
1
Order By: Relevance
“…Among the hyaluronidases reported to be expressed in cartilage, HYAL-2 and SPAM-1 (PH-20) are the primary candidates for the extracellular degradation of HA, as both enzymes are known to be active at neutral pH and are expressed at the cell surface of chondrocytes (Cherr et al ., 1996; Rai et al ., 2001; El Hajjaji et al ., 2005). However, high release and extensive HA degradation observed in the OSM cultures, suggest the presence of a hyaluronidase activity within the ECM (Durigova et al ., 2008a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the hyaluronidases reported to be expressed in cartilage, HYAL-2 and SPAM-1 (PH-20) are the primary candidates for the extracellular degradation of HA, as both enzymes are known to be active at neutral pH and are expressed at the cell surface of chondrocytes (Cherr et al ., 1996; Rai et al ., 2001; El Hajjaji et al ., 2005). However, high release and extensive HA degradation observed in the OSM cultures, suggest the presence of a hyaluronidase activity within the ECM (Durigova et al ., 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that membrane-bound HYAL-2 and/or SPAM-1 are released into the ECM through phospholipase action in the presence of OSM. In addition, it has been shown that proinflammatory cytokines such as IL-1β or TNFα can induce the gene expression and activity of both hyaluronidases in articular chondrocytes (Flannery et al ., 1998; El Hajjaji et al ., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The exception was the difference in the dry mass of the gels with the 3:7 −Col formulation, where a small but significant change in mass occurred. Under pro-inflammatory conditions, it has been demonstrated that chondrocyte hyaluronidase activity is upregulated. In OA, this upregulation of hyaluronidase activity is responsible for the fragmentation of HA and the release of aggrecan from the cartilage. Hyaluronidase can be both cell-membrane-bound , and extracellular .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is used in medicine in conjunction with other drugs to speed their dispersion and delivery. Some bacteria, such as Staphylococcus aurens, Streptococcus pyogenes and Clostridium perfringens produce hyaluronidase to hydrolysis of hyaluronic acid as means of increasing mobility through the body's tissues (Ponnuraj & Jedrzejas 2000;Lin & Stern 2001;Lokeshwar et al 2002;Hajjaji et al 2005;Kim et al 2005;Girish & Kemparaju 2006;Necas et al 2008). Based on these data, HA probably acts as a chemical and biological defence barrier.…”
Section: Discussionmentioning
confidence: 99%